Rehabilitation outcomes at discharge from staged community-based brain injury rehabilitation: A retrospective cohort study (ABI-RESTaRT), Western Australia, 2011–2020 - Troeung, Lakkhina; Mann, Georgina; Cullinan, Lily; Wagland, Janet; Martini, Angelita (Frontiers in Neurology, 2022)
Objective: To evaluate change in functional independence, psychosocial functioning, and goal attainment at discharge from a slow-stream Staged Community-Based Brain Injury Rehabilitation (SCBIR) service in Western Australia, 2011-2020. Methods: Retrospective cohort study of n=323 adults with acquired brain injury (ABI) enrolled in a post-acute SCBIR service compared against a control cohort of n=312 with ABI admitted to three non-rehabilitation programs (n=312). Outcome measures were the UK Functional Independence Measure and Functional Assessment Measure (FIM+FAM), Mayo Portland Adaptability Inventory-4 (MPAI-4), and Goal Attainment Scale. Change in FIM+FAM and MPAI-4 scores and predictors of goal attainment at discharge were evaluated using multilevel mixed-effects regression. Results: Median SCBIR length of stay was 20.5 months. Rehabilitation clients demonstrated clinically significant functional gains at discharge, with an adjusted mean change of +20.3, p<0.001 (FIM+FAM). Peak gains of +32.3 were observed after 24-30 months and clinically significant gains were observed 5years post-admission. Individuals discharged ≤6months had the smallest functional gains (+12.7). Small psychosocial improvements were evidenced at discharge, adjusted mean reduction = –2.9T, p<0.001 (MPAI-4) but not clinically significant. 47% of rehabilitation clients achieved their goals at the expected level or higher at discharge. Compared to the control, rehabilitation clients evidenced significantly greater functional gains and psychosocial improvement but lower goal attainment. Significant predictors of goal attainment at discharge were >2years since injury, higher cognitive function and higher emotional adjustment at admission. Conclusions: Functional recovery after ABI is a gradual process. SCBIR is effective for functional rehabilitation post-injury but can be improved to achieve clinically meaningful psychosocial improvement.